2011
DOI: 10.1007/s10499-011-9486-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VIE (Visible Implant Elastomer) and PIT (Passive Integrated Transponder) physical tagging systems for the identification of red porgy fingerlings (Pagrus pagrus)

Abstract: The effect of two physical tagging systems, Visible Implant Elastomer (VIE) and Passive Integrated Transponder (PIT), was evaluated in red porgy (Pagrus pagrus) fingerlings, at different sizes. For VIE tagging, the weight classes were \1 and 1-5 g and no tag effect was detected on fish growth. There was a significant difference in mortality between tagged and untagged \1 g fish, but not for the 1-5 g fish. The tag loss rate was null for all sizes, however, tags showed fragmentation. This partial tag loss was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
(105 reference statements)
3
20
1
2
Order By: Relevance
“…The majority of mortality (80%) occurred in fish 80 to 84 mm FL. This is in agreement with results from other studies that typically report higher mortalities in smaller individuals following tagging [18,21,24,25]. For example, Acolas et al [21] demonstrated that increases in length of juvenile brown trout (41 to 70 mm FL) significantly enhanced the probability of survival after implantation of 11.5 mm PIT tags.…”
Section: Mortalitysupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of mortality (80%) occurred in fish 80 to 84 mm FL. This is in agreement with results from other studies that typically report higher mortalities in smaller individuals following tagging [18,21,24,25]. For example, Acolas et al [21] demonstrated that increases in length of juvenile brown trout (41 to 70 mm FL) significantly enhanced the probability of survival after implantation of 11.5 mm PIT tags.…”
Section: Mortalitysupporting
confidence: 90%
“…A growing number of studies have addressed the adverse effects of PIT tagging on smaller fish and/or various life stages [12][13][14][15][16][17][18]. In juvenile salmonids, the impact of smaller PIT tags (11 to 12 mm) on growth and mortality have generally been negligible (for example, brown trout Salmo trutta [3]; Atlantic salmon Salmo salar [19]) and tag retention rates are usually high (that is, 97% to 100% [3,19,20], see [21] for an exception).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality, stress by handling and tag losses are among the causes of low recapture rates (Porto et al, 1999;Smithson, Johnston, 1999 Josephson et al, 2008;Carvalho-Souza et al, 2010;Soula et al, 2012) as well as low mortality caused by tagging procedures (e.g. Riley et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Las diferencias anatómicas, las diferentes condiciones de calidad de agua, las diversas magnitudes de resistencia, la susceptibilidad a la manipulación y términos de crecimiento, son unas de las razones que fundamentan su evaluación para cada especie (Davis et al, 2004, Jerry et al, 2001. En este sentido, para este estudio la ausencia de diferencias en el peso, talla y tasa de crecimiento específica entre peces marcados y no marcados en ambos experimentos, concuerda con lo reportado por Soula et al, (2012) en el bocinegro (Pagrus pagrus), quien evaluó el VIE en relación con el crecimiento, mortalidad, tiempo de manejo y tasa de perdida, encontrando que no existió efecto alguno sobre las variables, al igual que lo demostrado por otros autores (Soula et al, 2009, Zeeh y Wood, 2009, Liu et al, 2011. De igual manera revela que no hay efecto sobre el crecimiento de los peces de 4.59 y 8.9 g. Estos pesos en promedio demuestran que son los más adecuados para iniciar el marcaje con VIE, según estudios similares que han examinado su efecto en otras especies de peces, por ejemplo, el nulo efecto sobre el crecimiento fue demostrado en peces de dorada (Sparus auratus L) de 7 a 18 gramos (Astorga et al, 2005), en peces de bocinegro de 2 gramos, de igual manera como lo mencionó Jerry et al, (2001).…”
Section: Discussionunclassified
“…En relación con la retención del implante, se han referenciado diferentes estimados como por ejemplo Soula et al, (2012), quienes obtuvieron 75% de retención en bocinegro durante 15 y 30 días de estudio en dos tallas diferentes. Para este estudio de 30 días, un 94% en promedio para la posición corporal del dorso demuestra una elevada confiabilidad en su uso, por encima del 57.5% obtenido en el opérculo, reconociendo que aún falta evaluar esta variable por mucho más tiempo.…”
Section: Experimentounclassified